Neorealism and the Organization of American States (OAS): An Examination of CARICOM Rationality Toward Venezuela and the United States. (November 2019) - Johnson, Stephen
Since 2017, CARICOM member states have been divided in the positions they take on Organization of American States (OAS) resolutions addressing political instability in Venezuela. This article uses a neorealism framework to determine whether or not the provision of energy investments by Venezuela and the United States to CARICOM member countries is an attempt on their part to skew the OAS voting mechanism in their national interests. The article also examines the extent to which CARICOM member states' response to Venezuela's and United States' interest in the OAS demonstrates a pattern of rationality. The findings suggest that though the OAS provides a medium for states to negotiate mutually beneficial solutions, states are rational actors and even where they do corporate, dominant states may try to manifest their self-interest.